Measurement and sources of technical inefficiency : some evidence from the Sudanese Islamic bank - Abdullah, Naziruddin; Saaid, Abd Elrhman Elzahi (Universiti Utara Malaysia, 2003)
The establishment of Islamic banks that started in many parts of the Muslim countries some years ago has become a fact. However, this phenomenon needs to be justified empirically. Sudan has adopted Islamic principles for its entire banking industry. This has put the spotlight on the performance of the Islamic banks in the Sudan. In this paper the stochastic cost frontier function with a time series of cross-section data on Sudanese Islamic banks is used. The error terms are decomposed into v and u , which represent random noise and technical inefficiency, respectively. The banks in the sample have been divided into three categories, namely national banks, private domestic banks, and foreign joint venture banks. The technical efficiency was measured and the sources of ineficiency were investigated. The results showed that all banks in these groups were technically inefficient. The results also reveal that the national banks and private domestic banks were more technically inefficient than the foreign joint venture banks. The sources of ineficiency are attributed to the ownership, lack of banking technologies, severe economic sanctions and the lack of managing the high risk of the Islamic financing modes. This result has very good policy implications for the recent Sudanese government privatization policy regarding its national banks.